2020
DOI: 10.5812/jssc.103245
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Non-Alcoholic Fatty Liver Disease (NAFLD) Diagnosed by Controlled Attenuation Parameter on Transient Elastography and Its Predisposing Factors in Psoriasis

Abstract: Background: Psoriasis patients have an increased risk for non-alcoholic fatty liver disease (NAFLD). Controlled attenuation parameter (CAP) on transient elastography is more sensitive than abdominal ultrasonography in detecting liver steatosis. Objectives: To determine the prevalence of NAFLD in psoriasis and to identify its predisposing factors. Methods: A cross-sectional study was performed involving 109 psoriasis patients aged > 18 years in two tertiary dermatology clinics in Kuala Lumpur. Patients on hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Forty-one studies [12–14,18,33–69] were included in the meta-analysis that 19 studies were case–control studies and 22 studies had no control groups (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-one studies [12–14,18,33–69] were included in the meta-analysis that 19 studies were case–control studies and 22 studies had no control groups (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Gaspari, 2016 [57] Italy Caucasian 33/53 -54.8 PsA Not described Madanagobalane, 2012 [18] India Xu, 2017 [69] China Asian 250/439 -45.6 MSP US, liver test, exclusion of other liver diseases Torbator, 2022 [67] UK Caucasian 30/57 -55.5 NR US, liver test, exclusion of other liver diseases Tsai, 2011 [14] Taiwan Asian 223/51,800 434/207,200 46.4 MSP ICD Farias, 2011 [52] Chile Mixed 14/100 138/4928 43 NR Not described Kamil, 2019 [64] Malaysia Asian 93/109 -53 NR US, liver test, exclusion of other liver diseases Van Der Voort, 2016 [68] Netherlands Three previous meta-analyses [22][23][24] reported the association of NAFLD in psoriatic patients. One meta-analysis [23] suggested that the association was independent of confounding factors and body mass index, Psoriatic Area Severity Index scores, and liver function test components were significant risk factors for the association.…”
Section: Discussionmentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD) is one of the highly prevalent metabolic diseases/complications in patients with psoriasis, especially obese ones [ 2 , 3 ]. The estimated percentage of NAFLD in patients with psoriasis is 85% [ 4 , 5 ] but the cause of this high percentage is not fully explained [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD is expected to take on a predominant role as the leading aetiology of advanced liver disease in the forthcoming decades [ 1 ]. NAFLD is a condition that progresses from simple fatty liver (steatosis) to a severe form of non-alcoholic steatohepatitis (NASH) [ 2 ], which can result in irreparable organ damage, liver fibrosis, and hepatocellular carcinoma (HCC) in rare instances [ 3 ]. In general, an unbalanced diet and a lack of physical activity are the main causes of NAFLD [ 4 ].…”
Section: Introductionmentioning
confidence: 99%